Application of the Grey Model in One-Dimensional Long-Term Creep Analysis of Coral Mud From the South China Sea - Weng, He; Shen, Yang; Deng, Jue; Xu, Jun-hong; Ma, Ke (Frontiers in Physics, 2022)
Coral mud is widely distributed in the South China Sea. Studying deformation laws of coral mud is important to the infrastructure development in the South China Sea. In this paper, a one-dimensional oedometer test of coral mud under near-natural conditions is performed. The exponential fitting model, Burgers model and ODGM model are used to analyse the time-strain relationship of coral mud under different vertical pressures. The self-fitting accuracy and prediction accuracy of the three models under different vertical pressures are compared. Then, the number of data points used in the model was reduced, and the associated change in accuracy and model stability of the three models were analysed. The study found that the ODGM model has high self-fitting, high prediction accuracy, and a high model stability when the number of data points is reduced, which describe the long-term nonlinear deformation of coral mud more accurately.